Shortnose sturgeon (Acipenser brevirostrum) of the Saco River Estuary: Assessment of a unique habitat. (6th April 2018) - Hodgdon, C. T.; Tennenhouse, C.; Koh, W. Y.; Fox, J.; Sulikowski, J. A.
Summary: The shortnose sturgeon ( Acipenser brevirostrum ; SNS) is an endangered fish that thrives in large river systems along the U.S. east coast. Despite the endangered status, our understanding of this species' ecology is limited, especially regarding the importance of smaller river systems to their recovery. In 2010, the first sighting of SNS occurred in the Saco River estuary (SRE), Maine, a proportionately smaller system to other known drainages. To investigate the habitat usage of SNS within the SRE, an on‐going acoustic tagging study was initiated in 2011. In 2016, the collection of SRE abiotic data was coupled with the acoustic tagging study in an effort to establish which environmental parameters were most influential to SNS habitat preferences using Poisson regression. Aggregations of SNS in the SRE were concentrated rkm 6–8 and regression analyses revealed that water temperature, conductivity, acidity, and dissolved oxygen content were influential to these aggregations. Furthermore, SNS prey appears to be present and abundant throughout the estuary, and thus we hypothesize that SNS use the SRE as a foraging ground, but aggregate upriver due to the physiologically preferable and energetically optimal abiotic conditions.